2018
DOI: 10.25073/2525-2445/vnufs.4250
|View full text |Cite
|
Sign up to set email alerts
|

Reading Strategies Used by Vietnamese Efl and Esl University Students

Abstract: Reading comprehension is one of the most important factors in English language learning for all students because it is the basis of instruction in all aspects of language learning (Mikulecky, 2008). Comprehension is enhanced when the reader actively uses appropriate strategies in the reading process (Brown, 1980). This paper attempts to find out if there are any differences in the use of reading strategies between Vietnamese university students who learn English as a compulsory subject (EFL students) and those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
2
4
1
Order By: Relevance
“…This finding was slightly different from other studies which reported that cognitive strategy use has significant relationship to the students' reading comprehension score (e.g. Erni, 2021;Shang, 2011;Thuy, 2018;Ozek & Civelek, 2006;).…”
Section: Relationship Between Reading Strategy Used and The Reading S...contrasting
confidence: 99%
See 2 more Smart Citations
“…This finding was slightly different from other studies which reported that cognitive strategy use has significant relationship to the students' reading comprehension score (e.g. Erni, 2021;Shang, 2011;Thuy, 2018;Ozek & Civelek, 2006;).…”
Section: Relationship Between Reading Strategy Used and The Reading S...contrasting
confidence: 99%
“…It has been identified that one factor that contributes to learners' success in reading is reading strategies. For effective comprehension, further, Hernandez & Bulnes (2009) claim that being aware of reading comprehension strategies such as cognitive, metacognitive, and socio-affective, will allow students to become effective readers (Sun et al, 2021, Thuy, 2018Wang, 2016;Yapp et al, 2021) Reading strategies are defined as conscious actions employed to complete reading tasks particularly for comprehension (Barnett, 1989;Cohen, 1990;Garner,1987;Lehtonen, 2000). Hernandez and Bulnes (2009) assert that reading comprehension strategies are procedures involving objectives, plans and evaluations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results reveal that students use most of the autonomous language learning strategies at a high-frequency level. Furthermore, cognitive strategies appear to be used most frequently by these students, which is similar to the results of the study carried out by Channuan (2012), Shin andCrandall (2014), andNguyen (2018). These authors believe that cognitive strategies such as prediction and visualizing with given images effectively promote students' reading comprehension.…”
Section: Discussionsupporting
confidence: 84%
“…Research, including studies by Abdullah and Suan (2015), Khamkhong (2018), and others, indicates that Asian university students often lack critical reading skills and the higher order thinking necessary for tertiary education. While existing literature predominantly examines English language courses, contradictory findings emerge regarding the critical reading skills of Malaysian and Vietnamese students, with little focus on tertiary-level students in science or engineering (Azizi-Fini et al, 2015; Looi et al, 2022; Phan, 2023; Thuy, 2018). Critical reading, closely related to critical thinking (Paul and Elder, 2019), involves deep comprehension and a critical stance toward information that is pivotal in both personal and professional settings.…”
Section: Introductionmentioning
confidence: 99%